Instruksi Pendidikan Agama Kristen Dalam Mengembangkan Karakter dan Nilai-Nilai Spiritual dalam Era Digital 5.0 - Zebua, Sri Iman Putri; Giban, Yoel; Karlau, Sensius Amon (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2024)
In this technological era, many changes have occurred in everyday life, including Christian religious education. In situations like this, Christian religious education instruction plays a crucial role in building strong student characters and spiritual values relevant to the current situation. Christian religious education instruction in the current digital era pays attention to specific features of technology usage. Firstly, Christian religious education institutions have the ability to adapt to technological advancements and utilize them to effectively and efficiently deliver religious messages through the use of digital platforms and social media to build online communities and serve as references for sharing religious teachings. Christian religious education emphasizes the formation of strong character. Students are encouraged to be honest, responsible, and faithful in using technology in this challenging digital era. Christian religious education can develop spiritual values relevant to technological advancements, such as responsible usage, honesty in sharing information, and privacy protection. This includes the ability to use technology in a healthy manner, such as avoiding excessive dependency and controlling usage time. It is crucial for students to understand how to apply these principles in online interactions and use technology for their own and others' well-being. The researcher will discuss